Book Review: ‘Till We Win - India’s fight against the COVID-19 Pandemic’ - Kakkar, Rakesh; Aggarwal, Pradeep (Indian Journal of Community Health, 2020)
‘Till We Win’ is a book which provides a comprehensive overview of India’s journey. It deliberates how India, as a nation, fought and continue to fight against the novel coronavirus, SARS CoV-2. It documents and analyses the COVID-19 pandemic responses and provides lessons for health systems strengthening. The book has four section and eleven chapters. The first section focuses upon why viruses are likely to cause pandemic and how human activities are increasing the risks of outbreaks and epidemics. The next section deliberates on India’s pandemic response and how the policies had evolved with every new emerging condition. The authors argue that none of the country was fully prepared for the pandemic of the such a magnitude which eventually had disrupted even ‘so called’ better performing health system.